Optimasi Penggunaan Material Besi Tulangan pada Konstruksi Bangunan Bertingkat dengan Metode Building Information Modeling - Yohanesio; Subrata Aditama K.A.UDA; Okta Meilawaty (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This research definitively compares Building Information Modeling (BIM) with conventional methods to optimize reinforcing bar usage in multi-story building construction. Reinforcing bars are high-value materials, accounting for 20-30% of construction material procurement costs. The BIM method uses Autodesk Revit for 3D modeling and reinforcement, and Cutting Optimization Pro software for cutting optimization. The conventional method uses AutoCAD and MS Excel. The analysis results clearly indicate that the BIM method is more efficient with a volume of 183,618.77 kg compared to the conventional method's 194,562.98 kg. BIM generates significant savings for D10 (14.51%), D13 (47.29%), and D16 (40.15%) diameter bars. BIM combined with Autodesk Revit automatically generates Bar Bending Schedules (BBS) that are integrated with 3D models. This approach ensures seamless updates, eliminates error risks, and delivers superior clash detection capabilities. BIM's waste optimization strategy achieved a significant reduction in total reinforcement waste by 13,288.28 kg, from 32,148.83 kg to 18,860.56 kg. This was accomplished through the use of precise 3D modeling, despite slight increases in waste observed in D13 and D16 due to differences in calculation approaches.